ASPEKTY SPORTOWE W REPERTUARZE POLSKICH GRUP KABARETOWYCH - Bańka, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The term game defines the style or behavior of a musician, performer, or actor, because certain features distinguish him from others through the interpreted role. Games whose rules are based on competition are mimic games or sports, while those based on illusion concern the type of theater. Fun is a complex cultural phenomenon that is closely related to other phenomena of collective life. In Latin, the term “ludus” means game, play, but also public shows and games. The Olympic Games are a popular sporting event. They do not only affect the sport field, but they penetrate deeply into the culture. They unite not only the community associated with the sports environment, but also entire nations and other communities. Many Polish cabaret groups present sporting events depicting performances of Polish representatives, successes, failures, the most famous athletes as well as the profession of the sports reporter.